lmplant of upper limb. - Danza, Rómulo; Mauro, Líber; Insaurralde, Oscar; de Vecchi, Jorge; Navarro, Teodoro; Gastambide, Carmelo (Cirugía del Uruguay, 1984)
Notice is given o! the first case of upper limb implant carried out in Uruguay. lt .began with a clear cut performed with el